A C‐terminal fragment of adhesion protein fibulin‐7 inhibits growth of murine breast tumor by regulating macrophage reprogramming. (1st May 2020) - Chakraborty, Papiya; Dash, Shiba Prasad; Dalpati, Nibedita; Kumar, Puneet; Jain, Deepali; Sarangi, Pranita P.
Abstract : Recent reports have shown that a C‐terminal fragment of adhesion protein Fibulin7 (Fbln7‐C) could demonstrate both antiangiogenic and anti‐inflammatory activities. The current study investigated the potential of Fbln7‐C as a modulator of tumor‐associated macrophages (TAMs) and its potential as an anticancer therapeutic. Our in vitro data show that Fbln7‐C could inhibit the tumor cell line (MDA‐MB‐231) supernatant‐induced reprogramming of human monocytes into immunosuppressive TAMs as indicated by higher expression of pERK1/2 and pSTAT1 molecules, and reduced expression of CD206 protein and arg1, ido, and vegf transcripts in monocytes cultured in the presence of Fbln7‐C compared to controls. Interestingly, Fbln7‐C‐treated macrophages retained their altered phenotype even after the removal of Fbln7‐C, and their secretome demonstrated anticancer activities. Finally, in a 4T1‐induced murine breast tumor model, intravenous administration of Fbln7‐C, following the appearance of measurable tumors, significantly reduced the growth and weight of the tumors. Detailed phenotypic analysis of the infiltrated monocyte/macrophage populations (F480 + Ly6G − CD11b + ) at day 23 postinduction showed a higher percentage of inflammatory monocytes (F480 + Ly6C hi CD11b + ) and a delayed differentiation into anti‐inflammatory TAMs as evident by their reduced levels of CD206 expression. In conclusion, the above data suggest that Fbln7‐C could regulate the tumor environment‐induced macrophage reprogramming and has the potential for cancer therapeutics. Abstract : Fibulin7 is a member of the fibulin family of secreted glycoproteins. Previous reports suggest that a C‐terminal fragment of fibulin7 (Fbln7‐C) may demonstrate anti‐angiogenic and anti‐inflammatory activities. Here, Pranita Sarangi and co‐authors show that Fbln7‐C can inhibit the polarization of macrophages in the tumor microenvironment in vitro via modulation of the STAT and ERK1/2 signaling pathways. Moreover, Fbln7‐C delayed the development of 4T1‐induced mammary tumors. Their data indicate that Fbln7‐C plays a part in tumor‐associated macrophage reprogramming and thus could have potential applications in cancer immunotherapy.